1997
DOI: 10.1002/mds.870120108
|View full text |Cite
|
Sign up to set email alerts
|

The neurological syndrome of infantile cobalamin deficiency: Developmental regression and involuntary movements

Abstract: Developmental regression is the presenting symptom of most infants with cobalamin (Vitamin B12) deficiency. We present a report of three infants with cobalamin deficiency in which the infants also developed a movement disorder. In each case the mother was a vegetarian and the infant was exclusively breast-fed. In two of the infants, a striking movement disorder consisting of a combination of tremor and myoclonus particularly involving face, tongue, and pharynx appeared 48 h after the initiation of treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0
10

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 28 publications
3
87
0
10
Order By: Relevance
“…B12 deficiency is well known to have neuropsychiatric consequences in adults (Zucker et al 1981) and adversely affect neurodevelopment during infancy (Graham et al 1992). In toddlers, severe B12 deficiency has been associated with developmental regression similar to that observed in ~33% of autistic children (Grattan-Smith et al 1997). It is provocative to note that the TCN2 GG variant would be expected to negatively affect B12 cofactor availability for the methionine synthase reaction just as the interaction between RFC-1 80G and MTHFR 677T alleles would be expected to reduce methylfolate availability for the same methionine synthase reaction.…”
Section: Discussionmentioning
confidence: 94%
“…B12 deficiency is well known to have neuropsychiatric consequences in adults (Zucker et al 1981) and adversely affect neurodevelopment during infancy (Graham et al 1992). In toddlers, severe B12 deficiency has been associated with developmental regression similar to that observed in ~33% of autistic children (Grattan-Smith et al 1997). It is provocative to note that the TCN2 GG variant would be expected to negatively affect B12 cofactor availability for the methionine synthase reaction just as the interaction between RFC-1 80G and MTHFR 677T alleles would be expected to reduce methylfolate availability for the same methionine synthase reaction.…”
Section: Discussionmentioning
confidence: 94%
“…The duration of movement disorder is 10-30 d. The severity, nature, and timing of movement disorder are highly variable [1,4,7]. Jadhav et al [9] first described nutritional vitamin B12 deficiency in 6 Indian infants aged 6-12 months that presented with megaloblastic anemia, psychomotor regression, and hyper pigmentation of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that congenital anomalies in homocysteine remethylation or an abnormality in the methionine synthetase reaction leads to neurological symptoms [3,15]. Grattan-Smith et al [4] suggested that movement disorder in such cases is due to hyper activation of metabolic pathways that contain vitamin B12, and temporary vitamin B12 or folate metabolism imbalance. Changes in the plasma concentration of various amino acids were observed in response to vitamin B12 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations